Performance Evaluation of Urban Road Sections on The Taman - Sepanjang Highway - MCA, Theresia; Sekartadji, Ratih; Putra, Kurnia Hadi; Kusumaningrum, Dewi; R, Rizki (Faculty of Civil Engeneering and Planning - ITATS, 2024)
munity activities which are dominated by shops, offices and education activities and are directly adjacent to dense residential communities. The volume of vehicles passing through this road is quite dense, such as motorbikes, light vehicles and heavy vehicles, plus side obstacles that disrupt the smooth flow of traffic, especially during peak hours. The method used for this research is the 1997 Indonesian Road Capacity Manual (MKJI) method and the main indicator is the degree of saturation (DS). The results of the analysis show that the performance of the Taman - Sepanjang Highway sections (Highway Kalijaten Segment and Ngelom Segment) in existing conditions does not meet the 1997 MKJI feasibility standards. The degree of saturation value for highway Kalijaten is 1.00 and highway Ngelom is 0.87. So both roads need to improve road performance. The alternatives are widening the road, the saturation degree (DS), widening the road and removing side obstacles, become a one-way road. By implementing those alternative, Taman - Sepanjang Highway was expected to meet degree of saturation by MKJI standard.